Valuing and understanding fish populations in the Anthropocene: key questions to address. Issue 3 (7th February 2018) - Obregón, C.; Lyndon, A. R.; Barker, J.; Christiansen, H.; Godley, B. J.; Kurland, S.; Piccolo, J. J.; Potts, R.; Short, R.; Tebb, A.; Mariani, S.
Abstract : Research on the values of fish populations and fisheries has primarily focused on bio‐economic aspects; a more nuanced and multidimensional perspective is mostly neglected. Although a range of social aspects is increasingly being considered in fisheries research, there is still no clear understanding as to how to include these additional values within management policies nor is there a cogent appreciation of the major knowledge gaps that should be tackled by future research. This paper results from a workshop held during the 50th anniversary symposium of the Fisheries Society of the British Isles at the University of Exeter, UK, in July 2017. Here, we aim to highlight the current knowledge gaps on the values of fish populations and fisheries thus directing future research. To this end, we present eight questions that are deeply relevant to understanding the values of fish populations and fisheries. These can be applied to all habitats and fisheries, including freshwater, estuarine and marine.